Optimal control and transmission delay analysis of the process layer business data in smart substation - Lei CHEN; Ruzhong LIN; Zaichao HUANG; Hui DENG; Xiangqun WANG; Jing TAO (Dianxin kexue)
In order to meet the requirements of high real-time performance in the process of the smart substation,the typical communication network architecture,the real-time requirement of data service and the composition of network data delay were analyzed from the two aspects of communication system.And a solution for optimizing the real-time performance of communication system was presented.